Environmental Effect of Zinc Oxide Metal Nano Additives in Microalgae Biodiesel in Diesel Engine. (17th February 2023) - Subbulakshmi, M.; Srujana, S.; ArifSenolSener,; Al Zubi, Mohammad A.; Kumar, Ravi; Natarajan, Shanthi; Gidebo, Tewodros Derese
Abstract : We investigated how to extract energy from algal oil and convert it to biodiesel by transesterification in this study. In addition to performing engine performance tests with varying quantities of fuel mixture, parameters such as power, hourly torque consumption, specific consumption, and emissions of dioxide and monoxide were evaluated as an alternate solution to the pollution problem caused by fossil fuels. A 5.2 kW diesel engine powered the engine. The production of algal oil-based biodiesel was carried out effectively. The algal oil extraction procedure resulted in the production of biodiesel, which was then blended with commercial diesel in the amounts of 20, 40, and 60%. The engine performance testing revealed no statistically significant difference between the power and torque delivered by the various commercial diesel blends. Both hourly and particular consumption showed an increase of 15% and 20%, respectively, regarding commercial diesel consumption. However, the most significant advantage is the reduction in pollutant emissions, as demonstrated by the reduction in carbon dioxide emissions by more than 20% in any mixture of commercial diesel and biodiesel when compared to commercial diesel.